PEMBANGUNAN APLIKASI RUNTRACKER DENGAN MENGGUNAKAN GPS PADA SMARTWATCH BERBASIS ANDROID WEAR - Niskarto Zendrato; Ester Yusianna Br Ginting (UPPM, 2017)
RunTracker is an application that uses smartphone technology (Smartphones) and smart watches (Smartwatch) based on Android Wear. Where the function of Smartwatch is to calculate the distance and time traveled by runners, and then synchronized to the Smartphone so that runners can know the distanceand time it takes. Smart watches that can calculate the distance traveled by a runner using GPS (Global Positioning System) technology. . GPS is a system for determining the location of the earth with the help of satellite signal synchronization. The location data, if collected periodically can be used to calculate thedistance traveled by an object. For the development of this application, the author uses an Android-based smart watch that has a GPS feature